PERBANDINGAN TOTAL RENDEMEN DAN SKRINING ANTIBAKTERI EKSTRAK ETANOL DAUN SIRIH HIJAU (Piper betle L.) SECARA MIKRODILUSI - rissa laila vifta (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2017)
The optimization of extraction procces for Sirih Hijau leaves (Piper betle L.) have been attempted. The aim of the research was to knowing the influence and the ratio of total yield on two different methods, that was using maceration and reflux method and followed by microbial antibacterial by microdilution test to show the qualitative value of MIC percentage of Sirih Hijau leaves extract against Escherichia coli and Staphylococcus aureus bacteria. The analysis was conducted descriptively for subsequent use as a basis to determined MIC percentage quantitatively. The result of extraction with two methods showed that the highest yield was yielded in reflux process with 18.5% rendement value with the weight ratio of 1: 5 to the maceration process. Phytochemical screening shows the ethanol extract of Sirih Hijau leaves contains flavonoid, saponins, and tannins compounds that have activated as antibacterial. The results of microbial antibacterial testing showed MIC percentage in Staphylococcus aureus at 5% and Eschericia coli at 3%. The test results indicate that Sirih HIjau leaves (Piper betle L.) have potential as an antibacterial candidate. Keyword : Sirih Hijau, reflux, maceration, antibacterial, microdilution